Optimization of two-dimensional gel electrophoresis protocols for boesenbergia rotunda in vitro suspension culture - Chong, T.E.; Teck, F.G.; Ming, W.S.; Rahman, N.A.; Khalid, N.; Karsani, S.A.; Othman, S.; Yusof, R. (2011)
Boesenbergia rotunda belongs to the Zingiberaceae family and is abundant in the Southeast Asia. It is widely used as food ingredient and traditional medicine. Biologically, the plant extract contains pharmaceutically important bioactive compounds that exhibit anti-HIV protease, antibacterial, antifungal, anti-inflammatory, anti-tumor and antioxidant activities. Proteomics approaches to study the proteins and/or enzymes involved in the biosynthesis of these compounds are challenging due to the complexity of plant samples and the presence of interfering substances. Here, we describe the development a highly robust and reproducible two-dimensional gel electrophoresis (2DE) protocols for resolving the proteome of B. rotunda suspension cultures.